Association of TLR6 gene polymorphisms with zootechnical parameters in Holstein cattle in northern Antioquia (2017)
Specialized dairy systems are one of the most important lines in the agricultural sector in Colombia and the world. Currently there are strategies, both of environmental management and animal breeding, seeking to optimize the production. TLR6 gene, as many others related to immunity, is proving to be a useful candidate for programs of Marker Assisted Selection (MAS). Four hundred thirty two Holstein cows from 4 municipalities of northern Antioquia were genotyped using PCR-RFLP for C1859A and A1980G polymorphism of TLR6 gene. Allelic frequencies of 57.87% were found for C allele and 42.13% for A allele of C1859A, and 57.99% for A allele and 42.01% for G allele of A1980G. Genotypic frequencies of C1859A were 84.26% and 15.74% for CA and CC, respectively, and no AA genotype for this polymorphism was found; phenotypic frequencies of A1980G were 25.93%, 64.12% and 9.95% for AA, GA and GG, respectively. Mixed models for repeated measures with random effect of the animal were used to determine the association between genotypes and milk yield, percentages of protein and fat, services per conception, calving interval, and SCS. Both polymorphisms were only significant (P0.01) on the SCS feature, being C allele of C1859A and A allele of A1980G the most favorable. TLR6 gene showed an effect on quality milk trait SCS, as expected for its immunological role in the response against bacteria, and can be postulated as molecular marker for selection against infectious diseases of importance in animal production, such as mastitis.